Cotton fabric functionalisation with menthol/PCL micro- and nano-capsules for comfort improvement. (3rd October 2015) - Mossotti, Raffaella; Ferri, Ada; Innocenti, Riccardo; Zelenková, Tereza; Dotti, Francesca; Marchisio, Daniele L.; Barresi, Antonello A.
Abstract: Objective : Cotton functionalisation with poly-ɛ-caprolactone (PCL) micro- and nano-capsules containing menthol was carried out with the aim of introducing a long-lasting refreshing sensation. Materials and methods : The preparation of the polymer micro- and nano-capsules was carried out by solvent displacement technique. A confined impinging jets mixer was used in order to ensure fast mixing and generate a homogeneous environment where PCL and menthol can self-assemble. Results : The micro- and nano-capsules and the functionalised fabrics were characterised by means of DSC, FT-IR spectroscopy and SEM imaging. Micro- and nano-capsules of different size, from about 200 to about 1200 nm, were obtained varying menthol to PCL ratio (from 0.76 to 8), overall concentration and flow rate (i.e. mixing conditions). The inclusion of menthol was confirmed by DSC analysis. Discussion and conclusion : A patch test was carried out by 10 volunteers. Micro-capsules were found to be effective in conferring the fabric a refreshing sensation without altering skin physiology.